2018
DOI: 10.1016/j.ijid.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the yield of tuberculosis among contacts of multidrug-resistant and drug-sensitive tuberculosis patients in Ethiopia using GeneXpert as a primary diagnostic test

Abstract: The yield of TB among contacts of MDR-TB and DS-TB patients using GeneXpert was high as compared to the population-level prevalence. The likelihood of diagnosing rifampicin-resistant TB among contacts of MDR-TB index cases was higher in comparison with contacts of DS-TB index cases. The use of GeneXpert in DS-TB contact investigation has the added advantage of diagnosing rifampicin-resistant TB cases when compared to the use of the nationally recommended acid-fast bacillus (AFB) microscopy for DS-TB contact in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
1
6
1
Order By: Relevance
“…But out of 14 study subjects who had a history of contact with DS-TB only 1 had RR-TB result. 32 Similarly, in the current study, only one study subject developed RR-TB. Several studies in Ethiopia 7,8,15 and elsewhere 33,34 indicated that a history of previous TB treatment had strong association with the development of PTB and MDR-TB; whereas in the present study it was not associated with PTB.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…But out of 14 study subjects who had a history of contact with DS-TB only 1 had RR-TB result. 32 Similarly, in the current study, only one study subject developed RR-TB. Several studies in Ethiopia 7,8,15 and elsewhere 33,34 indicated that a history of previous TB treatment had strong association with the development of PTB and MDR-TB; whereas in the present study it was not associated with PTB.…”
Section: Discussionsupporting
confidence: 48%
“…12,31 Another study in Ethiopia indicated the prevalence of TB among presumptive PTB suspected who had contacts with MDR-TB patients was 45% and among presumptive PTB suspected who had contacts with DS-TB patients was 34%. 32 Having a contact history with MDR-TB infected cases was an important predictor (8/9) to develop RR-TB. But out of 14 study subjects who had a history of contact with DS-TB only 1 had RR-TB result.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, a facility-based study on childhood TB screening in rural Pakistan identified 390 additional children with TB through contact tracing [33]. Studies from the southern region of Ethiopia [37], Amhara and Oromia regions [38][39][40] have shown that contact tracing can serve as a good entry point for IPT provision. However, this has not been replicated in all countries as shown by a study in Botswana attributing the low coverage of IPT to a poor implementation of contact tracing [41].…”
Section: Plos Onementioning
confidence: 99%
“…However, ACF interventions identify people earlier in their disease history and possibly with lower bacillary loads and a negative sputum examination [2,5]. ACF algorithms increasingly include Xpert MTB/RIF testing [11][12][13], which has a higher sensitivity than sputum smear microscopy (SSM) [14]. However, if the number needed to test (NNT) with Xpert MTB/RIF to diagnose one case with BC PTB is high, this approach is costly and CLIN PTB is overlooked [5].…”
Section: Introductionmentioning
confidence: 99%